Integrating a computational fluid dynamics simulation and visualization with a 3D virtual walk through - a case study of Putrajaya - Jahn Kassim, Puteri Shireen; Ali, Maisarah; Abdul Majid, Noor Hanita; Ibrahim, Mansor (Springer Berlin Heidelberg, 2008)
This paper discusses the possibilities of applying Virtual Reality technologies within an analysis and presentations of the results and visualization output of a computational fluid dynamics simulation study of an urban master plan proposal with a focus on semi-outdoor spaces in selected areas. The environmental performance analysis was conducted to make an assessment in terms of air flow with the aim to enhance thermal comfort and predict the outcome of extreme wind events in the locality. This includes the investigation of the occurrence of wind-tunneling phenomena linked to pedestrian discomfort. The numerical and visual output of the simulation was used as a framework to integrate environmental performance data with a walk through of pedestrian walkways in selected area in Precinct $ of the Putrajaya Master Plan. Hence the paper is divided into two aspects i.e. the results of the Computational Fluid Dynamics (CFD) analysis and an example of how the data or graphical output is integrated with a virtual walk through of the selected 'parcel' or area.